Barrier properties of pullulan/starch based films modified with lauric acid - Ahmad, Mazatusziha; Vijayakumaran, Kanchana (Penerbit UTHM, 2017)
Enormous attention has been given in developing active food packaging materials in order to reduce the environmental effects caused by conventional packages. Recent scenario has turned into developing the food packaging materials based on biodegradable polymers such as starch-based materials. Starch, an agricultural raw material was chosen to be developed as it is widely available in nature, renewable and cheap. In this study, the potential of pullulan modified starch based films was investigated with the incorporation of lauric acid. Three types of film were prepared which are starch as control, starch/pullulan as well as starch/pullulan/lauric acid via casting technique. The barrier properties of these blends were assessed via Water Vapor Transmission Rate (WVTR. Further characterization of the blends was conducted via Fourier Transform Infrared Spectroscopy (FTIR) and the surface morphology of the film by Scanning Electron Microscopy (SEM). The results showed that the control films, starch exhibits the highest WVTR. The presence of lauric acid at highest composition of pullulan reduced the WVTR due to the hydrophobicity of the lauric acid. The C-H bond between starch, pullulan and lauric acid was detected via FTIR. The occurrence of peaks attributed to hydrogen bonding and OH group of starch. The composition which exhibited good water vapor resistant is starch modified pullulan at 7:3 ratio incorporated with lauric acid.